2021
DOI: 10.32890/ijib2021.6.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Bank Specific and Macroeconomic Factors Influencing Islamic Banks Deposits

Abstract: Deposits are like the bloodline for banks as they determine banks' lending capacity and a country's economic savings. However, the existence of a dual banking system poses a challenge to Malaysian Islamic banks competing for deposits. Despite this problem, few investigations were done to comprehensively identify the factors that could help banks attract deposits, particularly for Islamic banks. The purpose of this paper is to fill this gap on deposits of 16 Islamic banks in Malaysia. Secondary data from the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Some studies have shown that profit-sharing rates have a positive and significant effect on savings and financing (Irwanto & Hendrawati, 2020). The level of profit sharing has a substantial relationship to the public interest in placing their savings in Islamic banks (Ab Rahman et al, 2021). In addition, profit sharing has been shown to have a positive and significant influence on customers' decisions in choosing to save in Islamic banks (Mubarok, Hamid, & Arif, 2020).…”
Section: Profit-sharing Ratementioning
confidence: 99%
“…Some studies have shown that profit-sharing rates have a positive and significant effect on savings and financing (Irwanto & Hendrawati, 2020). The level of profit sharing has a substantial relationship to the public interest in placing their savings in Islamic banks (Ab Rahman et al, 2021). In addition, profit sharing has been shown to have a positive and significant influence on customers' decisions in choosing to save in Islamic banks (Mubarok, Hamid, & Arif, 2020).…”
Section: Profit-sharing Ratementioning
confidence: 99%